دراسة متغيرات انتشار الحزم الغاوصية في الفراغ الحر ومحاكاتها لأنواع مختلفة من الليزرات باستخدام MATLAB (Latakia University Journal -Basic Sciences Series, 2018)
يقدم هذا البحث دراسة تحليلية لمتغيرات انتشار الحزم الغاوصية من النمط الأساسي TEM00 في في أثناء انتشارها في الفراغ الحر بين مستويين مختلفين، الأول الممثل بموضع خصر الحزمة عند  والثاني الموازي له والممثل بأبعاد مختلفة لقيمz  المتناقصة والمتصاعدة، التي تنتشر بشكل متناظر بين طرفي خصر الحزمة الغاوصية وفق المحور z باستخدام تقنية الطيف الزاوي لأنواع مختلفة من الليزرات الغازية وليزرات الأجسام الصلبة ومن ثم محاكاتها عددياً باستخدام كل من البرنامجين Borland C++ builder 6 و MATALAB للحصول على الأشكال الهندسية ثنائية وثلاثية الأبعاد لتوزع شدة الإضاءة للحزمة الغاوصية وانزياح طورها وكذلك إيجاد توزع السعة العقدية للحقل الكهربائي للحزمة الغاوصية وتمثيلها فراغياً بقسميه الحقيقي والتخيلي. كما تم وصف انتشار الحزم الغاوصية في الفراغ الحر بدراسة كل من تغيرات نصف عرض الحزمة الغاوصية W(z) ونصف قطر انحناء جبهة الموجة R(z) كتوابع لأبعاد مختلفة وفق منحى انتشار  zللحزمة الليزرية من النمط الأساسي TEM00 في في أثناء انتشارها في الفراغ الحر باستخدام تقنية الطيف الزاوي. We present an analytical study of the propagation of Gaussian beams variables of the fundamental mode TEM00 during its propagation in free space between two different planes, the first plane is represented by a location of the beam waist; that is, when z = 0; to the second parallel plane is represented by different locations for decreasing and increasing values, which propagate symmetrically between both sides of the Gaussian beam waist according to the z-axis, using the angular spectrum technique for different types of lasers (gas and solid bodies) and then the numerical simulation using both programs: Borland C++builder 6 and MATLAB, in order to get the 2D and 3D geometrical shapes of the intensity of Gaussian beams illumination and the shift of its phase, and also to get the complex amplitude of Gaussian beams electrical field and its three-dimensional representation with its real and imaginary parts. A description of the Gaussian beams propagation in free space has also been done via the study of the variables of the Gaussian beam radius (half width of beam) W(z) and the radius of curvature R(z) of the wave front by the functionality of different locations according to the propagation of the laser beam along the - axis of Gaussian beam of the fundamental mode TEM00 during its propagation in free space using the angular spectrum technique.